Strengthening the Resilience of the Siponjot Village Community through Non-Formal Education and Planting Productive Trees for Disaster Mitigation and Welfare Improvement - Muhammadin Hamid; Syahrul Humaidi; Nursal; Noor Haida Mohd Kaus; Nazwa Armi; Utami Ahda Surya; Zahwan Asrof Zahirul Ubaid (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2026)
This Focus Group Discussion (FGD) aims to formulate strategies to strengthen the resilience of the Siponjot Village community through non-formal education and the planting of productive trees as efforts toward disaster mitigation and welfare improvement. Siponjot Village faces potential vulnerability to natural disasters such as landslides and floods, influenced by its geographical conditions and land-use patterns. Through the FGD, which involved village authorities, community leaders, farmer groups, and youth representatives, the need to enhance community capacity in environmental management through participatory educational approaches was identified. Non-formal education initiatives were designed to improve knowledge of disaster mitigation, land conservation, and skills in cultivating and managing productive trees. The planting of productive trees was selected as an integrated strategy because it strengthens soil structure, reduces disaster risks, and provides long-term economic benefits. The results of the FGD indicate increased collective awareness, collaborative commitment among stakeholders, and the development of a community-based action plan. Therefore, integrating non-formal education with productive tree planting represents a sustainable empowerment model to enhance both community resilience and rural welfare.